2021
DOI: 10.3389/fphar.2021.705623
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Mimetic Peptides Promote Corneal Epithelial Cell Regeneration

Abstract: The cornea of the eye is at risk for injury through constant exposure to the extraocular environment. A highly collagenous structure, the cornea contains several different types distributed across multiple layers. The anterior-most layer contains non-keratinized epithelial cells that serve as a barrier to environmental, microbial, and other insults. Renewal and migration of basal epithelial cells from the limbus involve critical interactions between secreted basement membranes, composed primarily of type IV co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…We have argued earlier that a tissue repair technology that reestablishes collagen fibrillar organization could restore both biomechanical and structural functions of collagen membranes and normal and healthy cell signaling ( Baratta R. O. et al, 2021 ), and ECM is increasingly viewed as an avenue for therapeutics ( Ren et al, 2015 ). The results we describe here for DRG cultures and in our experimental glaucoma model support the idea that CMP treatment could accelerate repair or protect against further axonal injury through the established action of CMPs intercalating into damaged collagen strands ( Chattopadhyay et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have argued earlier that a tissue repair technology that reestablishes collagen fibrillar organization could restore both biomechanical and structural functions of collagen membranes and normal and healthy cell signaling ( Baratta R. O. et al, 2021 ), and ECM is increasingly viewed as an avenue for therapeutics ( Ren et al, 2015 ). The results we describe here for DRG cultures and in our experimental glaucoma model support the idea that CMP treatment could accelerate repair or protect against further axonal injury through the established action of CMPs intercalating into damaged collagen strands ( Chattopadhyay et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The small number of CMPs tested here demonstrate modest reparative properties; we are examining whether other CMPs will show similar properties as we continue our studies with more extensive experimentation that incorporates additional outcome measures. A corollary is that this therapeutic approach could also reduce secondary inflammation that accelerates RGC degeneration in optic neuropathy that often arises with collagen degradation ( Baratta R. O. et al, 2021 ). A simple intravitreal injection of CMP that could affect wide-spread repair of ECM and promote RGC survival could offer an alternative for millions suffering from optic neuropathies, both chronic and acute.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that a collagen mimetic peptide (CMP 03A) prevented degradation of RGC axonal transport to the superior colliculus (SC), the primary target for RGC axons in rodents [ 24 , 25 ], following three weeks of microbead-induced elevations in intraocular pressure (IOP) [ 19 ]. This same CMP promoted healing of the corneal epithelium following acute corneal surface injury [ 58 ]. Additional members of the CMP family were efficacious in promoting neurite outgrowth from dorsal root ganglia cultures challenged by matrix metalloproteinase (MMP) digestion of collagen plating [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important work not only from the standpoint of restoring ECM structure, but also for reducing inflammation in local tissues [1]. We found that a CMP was efficacious in promoting the repair and structural integrity of the corneal epithelium following an acute injury [18]. Additional members of this CMP family promoted neurite outgrowth from dorsal root ganglia cultures following MMP-induced damage to the underlying collagen substrate [19].…”
Section: Introductionmentioning
confidence: 95%
“…Following treatment, adherence with CMP 13A was similar to that of intact collagen (p = 018). Recently, we found that a similarly structured CMP promoted repair of the corneal surface by enhancing migration of epithelial cells in vivo [18]. Here, we tested whether this same CMP(CMP 03A) similarly promotes adherence and migration of ARPE-19 cells using a transwell assay consisting of membrane inserts in which we coated only the basal (distal) side.…”
Section: Collagen Mimetic Peptides Promote Arpe-19 Cell Adherence And...mentioning
confidence: 99%